The influence of e-leaflet media in improving the skills of toddler Posyandu cadres - Syarifudin; Oktia Woro Kasmini Handayani; Chatila Maharani (Nursing and Health Sciences Journal (NHSJ), 2025)
Primary health service transformation implementation focuses on a lifecycle approach with promotive and preventive efforts and brings health services closer to cadres through Posyandu. Good integration of Primary Services requires efforts to improve the skills of posyandu cadres through E-Leaflet media. This study aims to determine the influence of e-leaflet media on improving toddler posyandu cadres' skills. This study used a quasi-experimental design with a one-size-fits-all posttest without a control group. The sample amounted to 43 posyandu cadres. The sampling technique is simple random sampling—data analysis with the Wilcoxon test. The p-value on the respondents' skills before and after being given the e-leaflet media was (p=0.001). There was a significant increase in skills after being given the e-leaflet media to the cadres of the Posyandu for toddlers. This statistically significant outcome confirms the efficacy of digital learning resources in strengthening frontline community health worker capabilities.